Strengthening stakeholders oversight roles in the NEITI process in Nigeria - Civil Society Legislative Advocacy Centre (Abuja, Nigeria : Civil Society Legislative Advocacy Centre, 2008)
The book shows what is possible when stakeholders of NEITI come together to exchange information and dialogue to ensure that the law is fully and effectively implemented.
oif 16/07/2018
Loans
Keywords: Nigeria Extractive Industries Transparency Initiative--Congresses.; Petroleum industry and trade; Mineral industries; Gas industry; Nigeria